Bleating, growling, barking, and spitting: Metaphorical extensions and valency patterns of verbs of speaking - Ivana Brač; Kristina Š. Despot; Branimir Belaj (PLoS ONE, 2025)
This corpus-based and qualitative study examines the valency patterns of Croatian verbs that encode verbal activity and belong to the semantic field of verbs of speaking through metaphorical and metonymic extensions, using a cognitive linguistics framework, specifically the usage-based model. The analysis focuses on examples such as the metaphoric use of animal sounds (e.g., blejati ‘to bleat’) and verbs associated with bodily processes (e.g., srati ‘to shit’), which often convey negative or stereotypical attitudes towards speakers or messages, or even extreme disdain. This paper contributes to the understanding of cross-domain figurative extensions of verb meanings and their valency adaptations. A dataset of 438 example sentences containing 152 verbs with figurative extensions targeting the domain of speaking was meticulously compiled from Croatian corpora. This dataset enabled a manual annotation and analysis of the transfer and adaptation of valency patterns across domains. The study addresses the following key questions: 1. What source domains are used for verbs of speaking as targets? 2. Do verbs retain the valency patterns of the source domain or adopt those of the target domain? 3. Is the passivization of transitive verbs possible in metaphorical contexts? The findings indicate that with a metaphorical shift in meaning, verbs often adopt new valency patterns from the target domain. Our examples of valency pattern change as a result of a metaphorical meaning shift demonstrate that verbs can appear with arguments not explicitly subcategorized by the verb itself.